DEVELOPMENT AND VALIDATION OF STABILITY INDICATING REVERSE PHASE LIQUID CHROMATOGRAPHIC METHOD FOR THE ASSAY OF AZELNIDIPINE IN BULK AND PHARMACEUTICAL FORMULATIONS - RAJAN V RELE.,; SWAPNIL A. SAWANT, (International Journal of Pharma and Bio Sciences, 2016)
A simple, rapid and accurate high performance liquid chromatography method is described for determination of azelnidipine from active pharmaceutical ingredients and its pharmaceutical dosage form. The separation of drug was achieved on Waters Symmetry C8 shield (15 x 4.6 mm i.d.) with 5 µ particle size column. It showed most favorable chromatographic pattern over the other columns. The mobile phase consisted of a mixture of 0.1% orthophosphoric acid in water and acetonitrile (60:40 % v/v). The detection was carried out at wavelength 256 nm. The mixture of 0.1% ( v/v) orthophosphoric acid in water and acetonitrile (60:40% (v/v)) was used as a diluent. The method was validated for system suitability, linearity, accuracy, precision, robustness, stability of sample solution. All the peaks of degradation products were resolved from the active pharmaceutical ingredient with significantly differ retention time. As the method could effectively separate the drug from the its degraded products. Hence above method can be also used for the study of stability indicating parameters.